(untitled) (Journal of Bangladesh Academy of Sciences, 2013)
Urinary tract infection (UTI) is increasingly rising in Bangladesh due to the development of resistance of causative pathogens against commonly prescribed antibiotics. Present study attempted to examine the prevalence of such uropathogens and their antibiogram profiles. Among 462 urine samples collected from patients with UTI, 100 were found to be culture positive. Escherichia coli (70%) was predominating, while Klebsiella spp. (11%) and Enterococcus spp. (6%) were also prevalent. About 96% uropathogens were sensitive against imipenem, and 75% against amikacin. The resistance rate of E. coli and Klebsiella spp. against ampicillin was 98.5 and 100%, respectively, and to cefotaxime, 84.3 and 72.8%, respectively. More than 80% resistance against these antibiotics was scored for other isolates. The frequency of drug resistance was found to be comparatively elevated in E. coli, Pseudomonas spp. and Proteus spp. Overall, the present investigation emphasized the need for routine screening of antibiotic resistance to promote effective medication against UTI. DOI: http://dx.doi.org/10.3329/jbas.v37i1.15681 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 1, 57-63, 2013